Pediatric cervicofacial actinomycosis: A case report - (:unkn) unknown (My University, 2004)
Cervicofacial actinomycosis affects many soft tissue and bony structures in the head and neck, and has both granulomatous and suppurative features. Pathogenesis of actinomycosis is still unclear, but trauma provides a portal of entry for the infection. It usually presents as a diffuse swelling with multiple sinus tracts containing macroscopic colonies of the organism known as "sulphur granules." Cervicofacial actinomycosis in children is rare. This article reports a case of actinomycosis in a 10-year-old-boy overlying the left ramus of the mandible.
Keywords: Actinomycosis; Child; Mandible